Integral of (x^2-2xy)+(2xy+y^2) dx
The solution
Detail solution
-
Integrate term-by-term:
-
Integrate term-by-term:
-
The integral of xn is n+1xn+1 when n=−1:
∫x2dx=3x3
-
The integral of a constant times a function is the constant times the integral of the function:
∫(−2xy)dx=−y∫2xdx
-
The integral of a constant times a function is the constant times the integral of the function:
∫2xdx=2∫xdx
-
The integral of xn is n+1xn+1 when n=−1:
∫xdx=2x2
So, the result is: x2
So, the result is: −x2y
The result is: 3x3−x2y
-
Integrate term-by-term:
-
The integral of a constant times a function is the constant times the integral of the function:
∫2xydx=y∫2xdx
-
The integral of a constant times a function is the constant times the integral of the function:
∫2xdx=2∫xdx
-
The integral of xn is n+1xn+1 when n=−1:
∫xdx=2x2
So, the result is: x2
So, the result is: x2y
-
The integral of a constant is the constant times the variable of integration:
∫y2dx=xy2
The result is: x2y+xy2
The result is: 3x3+xy2
-
Now simplify:
x(3x2+y2)
-
Add the constant of integration:
x(3x2+y2)+constant
The answer is:
x(3x2+y2)+constant
The answer (Indefinite)
[src]
/
| 3
| / 2 2\ x 2
| \x - 2*x*y + 2*x*y + y / dx = C + -- + x*y
| 3
/
∫((x2−2xy)+(2xy+y2))dx=C+3x3+xy2
y2+31
=
y2+31
Use the examples entering the upper and lower limits of integration.